PERJALANAN HIDUP DAN KREATIFITAS SANG PESINDHÃˆN - Batari Ayu Saraswati (Pascasarjana Institut Seni Indonesia Surakarta, 2013)
The article entitled â€œThe Life Journey and Creativity of the PesindhÃ¨nâ€ was in theory encouraged by a desire to understandaspects of the workmanship, the thoughts, and the success of Nyi Ngatirah who was moulded under the guidance anddirection of Ki Nartasabda. Nyi Ngatirah was chosen as the subject for the research because she was a skilled andsuccessful pesindhÃ¨n who created various innovations and made numerous developments and refinements to the cÃ©ngkokused in sindhÃ¨nan. In an endeavour to discover and study the workmanship of Nyi Ngatirah, the writer used akarawitanological approach which was integrated with a number of concepts from humanities and social disciplines in orderto complement and guide the analysis. In addition to studying her work, Nyi Ngatirah as a person was also studied. Theresults of the research showed that Nyi Ngatirah succeeded in making an important contribution for the development andcontinued existence of sindhÃ¨nan in particular and karawitan in general. In addition, the research showed that thecÃ©ngkok used in sindhÃ¨nan can always be developed in accordance with the ability of each performer and according to thecurrent day and age.Keywords: sindhenan, cengkok, and treatment.